2020
DOI: 10.1590/2317-4889202020190071
|View full text |Cite
|
Sign up to set email alerts
|

Lithogeochemistry and 3D geological modeling of the apatite-bearing Mesquita Sampaio beforsite, Jacupiranga alkaline complex, Brazil

Abstract: The Mesquita Sampaio beforsite is a mineral exploration area with apatite mineralization occurring near the northern portion of the Morro da Mina apatite deposit (Cajati Mine), in the Jacupiranga Alkaline Complex. This study presents the mineralogical, geochemical and 3D geological modeling data of this target. Four lithotypes are presented for Mesquita Sampaio: the fine-grained beforsite (FGB), the coarse-grained beforsite (CGB), the xenolith zone (XEN), and the jacupirangite ( JAC). The 3D geological model s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The main structural elements of carbonatites, such as joints, faults, dikes and fluid structures, are arranged in a radial and concentric manner, suggesting an intrusive body in the southern part of the occurrence, cut in turn by a posterior intrusion with a center in the north, resulted from 5 successive intrusions that led to five different types of carbonatites, according to structural, mineralogical and petrographic features (Barros 2001;Alves 2008). Faria Junior et al (2010 and Oliveira and Sant'Agostino (2020) cited the work developed by Saito et al (2004) in identifying a total of twelve geological units from the open pit, that considered not only geological characteristics but also relevant characteristics of the rock as ore in the beneficiation plant (Figure 3).…”
Section: Geology Overviewmentioning
confidence: 99%
“…The main structural elements of carbonatites, such as joints, faults, dikes and fluid structures, are arranged in a radial and concentric manner, suggesting an intrusive body in the southern part of the occurrence, cut in turn by a posterior intrusion with a center in the north, resulted from 5 successive intrusions that led to five different types of carbonatites, according to structural, mineralogical and petrographic features (Barros 2001;Alves 2008). Faria Junior et al (2010 and Oliveira and Sant'Agostino (2020) cited the work developed by Saito et al (2004) in identifying a total of twelve geological units from the open pit, that considered not only geological characteristics but also relevant characteristics of the rock as ore in the beneficiation plant (Figure 3).…”
Section: Geology Overviewmentioning
confidence: 99%
“…The main structural elements of carbonatites, such as joints, faults, dikes and fluid structures, are disposed in a radial and concentric aspect, suggesting an intrusive body from 5 successive intrusions that led to five different types of carbonatites, according to structural, mineralogical and petrographic features (Barros, 2001;Alves, 2008). Faria Junior et al (2010 and Oliveira & Sant'Agostino (2020) cited the work developed by Saito et al (2004) in the identification of a total of twelve geological units from the open pit, that considered not only geological characteristics but also relevant characteristics of the rock as ore in the beneficiation plant (Fig. 5).…”
Section: Geological Overviewmentioning
confidence: 99%
“…Drilling has demonstrated that the carbonatites extend in depth to at least 400 m below the sea level, with a general dip angle of 80 o , and the structures are mainly represented by a shear zone (fault), a set of joints and fractures (Alves, 2008). According to Oliveira & Sant'Agostino (2020), the fault zone corresponds to the main fault of a brittle shear regime that produced the main fault system and subsidiary faults, with N75W/subvertical direction.…”
Section: Geological Overviewmentioning
confidence: 99%
See 2 more Smart Citations